INSTITUTIONAL TRAPS» OF DIGITAL ECONOMY: CONCEPT AND METHODOLOGY OF RESEARCH - I. Penkova (Вестник Северо-Кавказского федерального университета)
The relevance of the study is due to the fact that socio-economic transformations are caused by the transition of the global community to overall digitalization, taking place on the basis of civilizational assumptions that influence current processes both positively and negatively. As a result, this creates institutional traps, which in the article are defined by authors. Likewise current processes require researches from the standpoint of the economic theory concerning qualitative and quantitative transformations occurring in industrial relations and caused by the increasing role of information and digitalization in economic and economical processes. The aim of the study is to solve the urgent fundamental scientiic problem of developing a methodological ground regarding the identiication and overcoming institutional traps, based on determining the degree of positive and negative effects of information on socio-economic development; to examine and justify the features and patterns of socio-economic changes associated with the growing digital economy in Russia and worldwide.